Report on intussusception in channel catfish Ictalurus punctatus (Rafinesque, 1818) from commercial farms in Mexico: A case study - Montelongo-Alfaro, Isidro O.; Rabago-Castro, Jaime L.; Sanchez-Martinez, Jesus Genaro; Benavides-Gonzalez, Flaviano; Cruz-Hernandez, Ned Ivan De La (Indian Journal of Fisheries, 2018)
Intussusception is a rare condition in fish, mainly reported from Asian countries and it is considered an emergent disease in China. This is the first report on intussusception case in channel catfish Ictalurus punctatus, cultured in floating cages in Mexico. Fishes were sampled during an outbreak with daily mortalities above 1.14%. Necropsy revealed intestinal intussusception, pale liver and hemorrhagic mesentery. Bacteriological analyses showed presence of Aeromonas sp. in internal organs and it is suggested that the presence of Aeromonas sp. is probably responsible for the observed condition.